Оптимізація управління якістю освітніх послуг українських вишів шляхом запровадження CRM систем - Гарник, Людмила Петрівна (My University, 2018)
Під впливом глобалізації за останні десятиріччя було кардинально змінено та переглянуто ставлення до спроможності освітян мобілізувати внутрішні культурні, інтелектуальні та духовні цінності для сприяння інноваційному розвитку українського суспільства. Сьогодні, у добу поліцентричної економічної системи, яка базується на знаннях та культурних цінностях, Україна, як і більшість країн світу, постала перед нагальною потребою гармонізації протиріч між елементами національної та міжнародної систем освіти. Відповідно до сучасних трендів, більшість провідних освітніх та навчально-дослідницьких закладів уже отримали визнані на міжнародному рівні сертифікати на свої СУЯ (ISO 9001:2015), які базуються на процесному підході та ризик-орієнтованому мисленні, що є випробуваними на практиці інструментами для конструювання та подальшої розбудови їх унікальних систем управління якістю освітніх послуг. Дослідження присвячено огляду та аналізу кращих світових практик і можливостей упровадження CRM систем для оптимізації та гармонізації вітчизняної системи освіти. Традиційно лідери нашої країни приділяють особливу увагу розвитку інтелектуального потенціалу так само, як і культурній та соціальній мобільності громадян України шляхом надання їм єдиних прав доступу до інноваційної освіти.

Under influence of globalization within last decades were cardinally changed and revised viewpoints on ability of educators to mobilize internal cultural, intellectual and spiritual values for acceleration of innovative development of Ukrainian society. Now in epoch of knowledgeand cultural-based polycentric economic system Ukraine like many other countries of the world have faced with essential need to mediate contradicts between elements of national and international educational systems. According to contemporary trends, numerous of leading educational and educational-research institutions have got internationally recognized certificates on their QMS (ISO 9001:2015), based on process approach and risqué-oriented thinking, that are practically approved instruments for construction and further development of their unique quality management systems. Research is devoted to observe and analysis of better world practices and possibility of implementation the CRM systems for optimization and harmonization of current Ukrainian educational system. Traditionally leaders of our country pay special attention to increasing of intellectual potential as like as cultural- and social flexibility of Ukrainian citizens by providing for them equal access to based on innovations education.
Optimization of educational services quality management in ukrainian higher educational institutions by implementation of CRM systems
Keywords: освітні послуги; якість освіти; CRM системи; економіка знань; система освіти; інновації; educational services; CRM systems; knowledge economics; national educational system; innovations